# ONESCHOOL.

NET Add Maths Formulae List: Form 4 (Update 18/9/08)
01 Functions
Absolute Value Function Inverse Function If

f ( x), if f ( x) ≥ 0 f ( x) − f ( x), if f ( x) < 0

y = f ( x) , then f −1 ( y) = x

Remember: Object = the value of x Image = the value of y or f(x) f(x) map onto itself means f(x) = x

ax 2 + bx + c = 0
where a, b, and c are constants and a ≠ 0. Forming Quadratic Equation From its Roots: If α and β are the roots of a quadratic equation

−b ± b 2 − 4 ac x= 2a
When the equation can not be factorized. Nature of Roots

α +β =−

b

a

αβ =

c a

b − 4 ac > 0 ⇔ two real and different roots b 2 − 4 ac = 0 ⇔ two real and equal roots b 2 − 4 ac < 0 ⇔ no real roots b 2 − 4 ac ≥ 0 ⇔ the roots are real

2

x 2 − (α + β ) x + αβ =0
or x 2 − (SoR) x + ( PoR) = 0

http://www.one-school.net/notes.html

1

General Form f ( x) = ax 2 + bx +

ONESCHOOL.NET
Completing the square: f ( x) = a( x + p) 2 +

c where a, b, and c are constants and a ≠ 0. *Note that the highest power of an unknown of a quadratic function is 2. (i) (ii) (iii) (iv)

q the value of x, x = − p min./max. value = q min./max. point = (− p, q) equation of axis of symmetry, x = − p

Alternative method: a > 0 ⇒ minimum ⇒ ∪ (smiling face) a < 0 ⇒ maximum ⇒ ∩ (sad face) c Quadratic Inequalities a > 0 and f ( x) > 0 a > 0 and f ( x) < 0 Nature of Roots b − 4ac > 0 ⇔ intersects two different points at x-axis b 2 − 4ac = 0 ⇔ touch one point at x-axis b 2 − 4ac < 0 ⇔ does not meet x-axis
2

f ( x) = ax 2 + bx +

a

b

a

b

x < a or x > b

a< x<b

04 Simultaneous Equations
To find the intersection point ⇒ solves simultaneous equation. Remember: substitute linear equation into non- linear equation.

http://www.one-school.net/notes.html

2

05 Indices and Logarithm
Fundamental if Indices Zero Index, Negative Index, Laws of Indices

ONESCHOOL.NET

a0 = 1 a −1 =
1 a

+ n a × annn = anmm×n n a m− a(a÷ )a a=b a (ab) = = m n m m n

a a ( )n = n b b

n

a b ) −1 = ( b a Fractional Index

an = a n
m

1

an =
Fundamental of Logarithm

n

am

Law of Logarithm

log a y = x ⇔ a x = y log a a = 1 log a a = x
x

log a mn = log a m + log a n log
a

m n
n

log a 1 = 0

= log m − log na a

log a m = n log a m
Changing the Base

log a b =

log c b log c a

http://www.one-school.net/notes.html

3

06 Coordinate Geometry

ONESCHOOL.NET

Distance Between Point A and C =

(x1 − x2 )2 + (x1 − x2 )2
Gradient of line AC, m = Or y2 − y1 x2 − x1

⎛ y − int ercept ⎞ Gradient of a line, m = − ⎜ ⎟ ⎝ x − int ercept ⎠ Parallel Lines Perpendicular Lines

When 2 lines are parallel,

When 2 lines are perpendicular to each other, m1 × m2 =

m1 = m2 .

−1
Midpoint

A point dividing a segment of a line

Midpoint, M =

⎛ x1 + x2 y1 + y2 ⎞ , ⎜ 2 2 ⎟ ⎝ ⎠

A point dividing a segment of a line

P=

⎛ nx1 + mx2 ny1 + my2 , ⎞ ⎜ m+n ⎝ ⎠ m+n ⎟

http://www.one-school.net/notes.html

4

Area of triangle:

Area of Triangle =

1 2
1 2

A=

(

x1 y2 + x2 y 3 + x3 y1 ) −

(

x2 y1 + x3 y2 + x1 y3 )

Form of Equation of Straight Line General form
ax + by + c = 0

y= mx+

Intercept form x y + =1 a b a = x-intercept b = y-intercept m=b − a

c

m = gradient Equation of Straight Line Gradient (m) and 1 point (x1, y1) given y − y1 = m( x − x1

2 points, (x1, y1) and (x2, y2) given y − y1 = y2 −

x-intercept and y-intercept given x y + =1 a b

y1 Equation of perpendicular bisector ⇒ gets midpoint and gradient of perpendicular line. ) Information in a rhombus: A

B (i) (ii) (iii) (iv)

same length ⇒ AB = BC = CD = AD parallel lines ⇒ mAB = mCD or mAD = mBC diagonals (perpendicular) ⇒ mAC × mBD = −1 share same midpoint ⇒ BD midpoint AC = midpoint

D C (v)

any point ⇒ solve the simultaneous equations

Remember:

y-intercept ⇒ x = 0 cut y-axis ⇒ x = 0 x-intercept ⇒ y = 0 cut x-axis ⇒ y = 0 **point lies on the line ⇒ satisfy the equation ⇒ substitute the value of x and of y of the point into the equation.

Equation of Locus ( use the formula of distance) The equation of the locus of a moving point P( x, y) which is always at a constant distance (r) from a fixed point A ( x1 , y1 ) is PA = r
2 2 2

The equation of the locus of a moving point P( x, y) which is always at a constant distance from two fixed points A ( x1 , y1 ) and B ( x2 , y 2 ) with a ratio m : n is PA m = PB n

The equation of the locus of a moving point P( x, y) which is always equidistant from two fixed points A and B is the perpendicular bisector of the straight line AB. PA = PB 2 2 ( x) 2 x ) + ( y − y ) = ( x − x ) + ( y − y −
2 1 1 2 2

( x − x1 ) + ( y − y1 ) = r

( x − x ) 2 + ( y −1 y )2 m2 1 = 2 2 ( x − x ) + (y − 2 ) n y 2

More Formulae and Equation List: SPM Form 4 Physics - Formulae List SPM Form 5 Physics - Formulae List SPM Form 4 Chemistry - List of Chemical Reactions SPM Form 5 Chemistry - List of Chemical Reactions

All at 0O F 4DIPPM

OFU

07 Statistics
Measure of Central Tendency Ungrouped Data Mean x= Σx N Grouped Data Without Class Interval With Class Interval x= Σ fx Σ f x= Σ fx Σ f

x = mean Σx = sum of x x = value of the data
N = total number of the data

x = mean Σx = sum of x f = frequency x = value of the data

x = mean f = frequency x = class mark (lower limit+upper limit) = 2 ⎛1 N−F⎞ ⎟C m= L+ ⎜ 2 ⎝ fm ⎠ m = median L = Lower boundary of median class N = Number of data F = Total frequency before median class fm = Total frequency in median class c = Size class = (Upper boundary – lower boundary)

Median

m = TN +1
2

m = TN +1
2

When N is an odd number.

When N is an odd number.

TN + TN

TN + TN

m=

2

+1

2

2

m=

2

+1

2

2

When N is an even

When N is an even number.

Measure of Dispersion Ungrouped Data variance
2 ∑x 2

Grouped Data Without Class Interval With Class Interval

σ =

2

−x

σ =

2

∑ fx2 ∑f

−x

2

σ =

2

∑ fx2 ∑f

−x

2

σ = variance
Standard Deviation Σ

σ = variance
Σ

σ = variance
Σf

(

x−x

(

x−x

2

σ= σ=

)2
N
2

σ=

)

(

2

x−x)

N
2

σ= σ=

Σx −x2 N

Σx σ= −x2 N

Σf Σ fx 2 −x2

The variance is a measure of the mean for the square of the deviations from the mean. The standard deviation refers to the square root for the variance. Effects of data changes on Measures of Central Tendency and Measures of dispersion Data are changed uniformly with +k −k ×k ÷k −k ×k ÷k +k No changes No changes No changes ×k ×k 2 ×k ÷k ÷k 2 ÷k

Measures of Mean, median, mode Central Tendency Range , Interquartile Range Measures of Standard Deviation dispersion Variance

08 Circular Measures
Terminology

D

xo = ( x

×

π

x radians = ( x ×

180 ) degrees π

π × D 180

???

???

Length and Area

r = radius A = area s = arc length θ = angle l = length of chord

Arc Length:

Length of chord:

Area of Sector: A= 1 2 rθ 2

Area of Triangle: A= 1 2 r sin θ 2

Area of Segment: A= 1 2 r (θ − sin θ ) 2

s = rθ

l = 2r sin

θ 2

09 Differentiation
Gradient of a tangent of a line (curve or straight) dy dx = m( li) x
δ x→0

Differentiation of a Function I y= x dy n−1 = nx dx
n

δy δ

Differentiation of Algebraic Function Differentiation of a Constant y=a dy =0 dx Example y=2 dy =0 dx a is a constant

Example y = x3 dy = 3x 2 dx Differentiation of a Function II y = ax dy = ax1−1 = ax 0 = a dx Example y = 3x dy =3 dx

Differentiation of a Function III y = ax dy n−1 = a nx dx Example y = 2x 3 dy dx = 2 (3) x 2 = 6x 2
n

Chain Rule
n

ONESCHOOL.NET

y=u u and v are functions in x dy dy du = × dx du dx Example y = (2x 2 + 3)5

du u = 2x 2 + 3, therefore dx = 4x y = u 5 , therefore dy dy du = × dx du dx 4 = 5u × 4x = 5(2x 2 + 3) 4 × 4x = 20x(2 x 2 + 3) 4 dy 4 = 5u du

Differentiation of a Fractional Function 1 n x Rewrite y= y = x− n − n−1 dy −n = −nx = x n+1 dx Example 1 y= x y = x −1 dy −1 −2 = −1x = 2 dx x

Or differentiate directly y = (ax + b) n dy = n.a.(ax + b)n −1 dx y = (2x 2 + 3)5 dy = 5(2x 2 + 3) 4 × 4x = 20 x(2x 2 + 3) 4 dx

Law of Differentiation Sum and Difference Rule y=u±v dy dx = du u and v are functions in x dv ± dx dx

Example y = 2x 3 + 5x 2 dy = 2(3) x 2 + 5(2) x = 6x 2 + 10x dx

Product Rule y = uv dy dx =v du dx u and v are functions in x +u dx dv

Quotient Rule yu = v

ONESCHOOL.NET

u and v are functions in x

Example 3 2 y = (2x + 3)(3x − 2x − x) u=2x+ 3 du v = 3x 3 − 2x 2 − x dv = 9 x 2 − 4x − 1

du dv dy v dx − udx = 2 dx v Example 2 x y= 2x+1 v = 2x + 1 dv dx =2

=2

dx dx dy du dv =v +u dx dx dx

u = x2 du =2 x dx dy dx

=(3x 3 − 2x 2 − x)(2) + (2x + 3)(9x 2 − 4 x − 1) Or differentiate directly y = (2x + 3)(3x 3 − 2x 2 − x) dy
3 2 2

duv 2 dv v dx − udx =

dy dx

=

(2 x + 1)(2 x) − x 2 (2) (2 x2+ 1) 4x +2x−2
2

dx

= (3x − 2x

− x)(2) + (2x + 3) (9x

− 4x − 1) =

x (2x 2+ 1)

2

2x + 2 x = 2 (2 x + 1)

2

Or differentiate directly 2 x y= 2x+ 1 dy (2 x + 1)(2 x) − x 2 (2) = 2 dx (2 x + 1) 2x + 2 x 4 x +2x −2x = = (2x + 1) 2 (2 x + 1) 2
2 2 2

Gradients of tangents, Equation of tangent and Normal

ONESCHOOL.NET

Gradient of tangent at A(x1, y1): dy = gradient of tangent dx Equation of tangent: y − y1 = m( x − x1 ) Gradient of normal at A(x1, y1): mnormal = − If A(x1, y1) is a point on a line y = f(x), the gradient of the line (for a straight line) or the gradient of the dy tangent of the line (for a curve) is the value of dx when x = x1. Maximum and Minimum Point 1 mtangent

1 dy = gradient of normal − dx Equation of normal : y − y1 = m( x − x1 )

Turning point ⇒ At maximum point, dy =0 dx

dy =0 dx

d y 2 < 0 dx

2

At minimum point , dy =0 dx

d y 2 > 0 dx

2

Rates of Change Chain rule dA dA dr = × dt dr dt
-1

Small Changes and Approximation Small Change:

δy

If x changes at the rate of 5 cms

dx =5 dt

dy dy ≈ ⇒ δ y≈ ×δx δ x dx dx

Decreases/leaks/reduces ⇒ NEGATIVES values!!!

Approximation: ynew = yoriginal + δ y =y + x original dy dx ×δ

δ x = small changes in x

10 Solution of Triangle

ONESCHOOL.NET

Sine Rule: a b c = = sin A sin B sin C Use, when given 2 sides and 1 non included angle 2 angles and 1 side
a A b B A 180 – (A+B)

Cosine Rule:
a = b + c – 2bc cosA b2 = a 2 + c2 – 2ac cosB 2 2 2 c = a + b – 2ab cosC
2 2 2

Area of triangle:
a

C
b

b +c −a cos A = 2bc

2

2

2

A=

a

Use, when given 2 sides and 1 included angle 3 sides
a A b b a c

1 a b sin C 2

C is the included angle of sides a and b.

ONESCHOOL.NET
Case of AMBIGUITY
A If ∠C, the length AC and length AB remain unchanged, the point B can also be at point B′ where ∠ABC = acute and ∠A B′ C = obtuse. If ∠ABC = θ, thus ∠AB′C = 180 – θ .

180 - θ

θ

Remember : sinθ = sin (180° – θ) Case 2: When a = b sin A CB just touch the side opposite to C

C B B′ Case 1: When a < b sin A CB is too short to reach the side opposite to C.

Outcome: No solution Case 3: When a > b sin A but a < b. CB cuts the side opposite to C at 2 points

Outcome: 1 solution Case 4: When a > b sin A and a > b. CB cuts the side opposite to C at 1 points

Outcome: 2 solution Useful information:
b a c

Outcome: 1 solution In a right angled triangle, you may use the following to solve the problems. (i) Phythagoras Theorem: c = a 2 + b2 (ii) Trigonometry ratio: sin θ = c b , cos θ =c a , tan θ a = ½ (base)(height)
b

θ

(iii) Area =

11 Index Number
Price Index Composite index

ONESCHOOL.NET

I=

P1

×

I=

ΣWi I i ΣWi

100 P0 I = Price index / Index number I A,B × I B,C = I A,C ×100

I = Composite Index W = Weightage I = Price index